Immigration and offshoring: Two forces of globalisation and their impact on employment and the bargaining power of occupational groups - Michael Landesmann; Sandra M. Leitner (The Vienna Institute for International Economic Studies (wiiw), 2020)
This paper estimates conditional demand models and, using a joint approach for the period 2008-2017, examines the impact of immigration and different measures of offshoring on the labour demand and demand elasticities of native workers in four different types of occupational groups: managers/professionals, clerical workers, craft (skilled) workers and manual workers. The analysis is conducted using data for four EU economies: Austria, Belgium, France and Spain. Our results point to important and occupation-specific direct and indirect effects of immigration and offshoring. Both offshoring - particularly services offshoring - and immigration have negative direct employment effects on all occupations, but native clerks and manual workers are affected the most, and native managers/professionals the least. Generally, offshoring exerts a stronger direct negative employment effect than does immigration. Our results also identify an important (labour demand) elasticity-channel of immigration and offshoring and show that some groups of native workers can also actually gain from globalisation through an improvement in their wage-bargaining position. Overall, our results indicate a deterioration in the bargaining power of native manual workers arising from both immigration and offshoring; an improvement in the bargaining position of native craft workers in the case of both immigration and offshoring; and an improvement in the bargaining position of native clerical workers and managers/professionals in the case of offshoring only. Finally, our analysis of the cross-effects of immigration highlights the important role of migrant managers/professionals for the labour demand and demand elasticities (bargaining power) of native clerical workers, craft and manual workers.
Keywords: F16; F22; F66; 330; Offshoring; immigration; labour demand elasticity; bargaining power; occupations